2002
DOI: 10.2527/2002.803708x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean meal from roundup ready or conventional soybeans in diets for growing-finishing swine

Abstract: Dehulled soybean meal prepared from genetically modified, herbicide (glyphosate)-tolerant Roundup Ready soybeans containing the CP4 EPSPS protein and near-isogenic conventional soybeans were assessed in an experiment with growing-finishing pigs. The soybeans were grown in the yr 2000 under similar agronomic conditions except that the Roundup Ready soybeans were sprayed with Roundup herbicide. Both were processed at the same plant. The composition of the two types of soybeans and the processed soybean meal were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 10 publications
10
34
0
5
Order By: Relevance
“…The lack of an effect of transgenic wheat on carcass measures is similar to the findings of a number of studies that have evaluated Roundup Ready corn and soybean meal in pigs (Stanisiewski et al, 2001;Cromwell et al, 2002;Hyun et al, 2004) and broiler chickens (Hammond et al, 1996;Taylor et al, 2003a and2003b), and was to be expected given that there was no effect of the transgenic variety on growth performance in any of these studies.…”
Section: Carcass Measurementssupporting
confidence: 65%
See 2 more Smart Citations
“…The lack of an effect of transgenic wheat on carcass measures is similar to the findings of a number of studies that have evaluated Roundup Ready corn and soybean meal in pigs (Stanisiewski et al, 2001;Cromwell et al, 2002;Hyun et al, 2004) and broiler chickens (Hammond et al, 1996;Taylor et al, 2003a and2003b), and was to be expected given that there was no effect of the transgenic variety on growth performance in any of these studies.…”
Section: Carcass Measurementssupporting
confidence: 65%
“…Also, Gaines et al (2001) showed no difference in the digestible energy coefficients of Roundup Ready corn compared to a genetically similar corn hybrid that lacked the transgenic trait. Studies with Roundup Ready soybean meal containing the same genetic modification as the wheat used in the present study also showed no effect on the growth performance of pigs relative to the non-transgenic genetically similar control soybean meal (Cromwell et al, 2002). A number of other studies with a range of species that have compared the growth performance of animals fed Roundup Ready corn or soybean meal with that of animals fed the non-transgenic genetically similar or conventional commercial varieties have shown no negative impact on growth.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Studies assessing the acute nutritional value (around four weeks) or chronic nutritional value (up to 15 weeks) have already be carried out using rats, mice, pigs, chicken, fi sh, nothura and cattle (Hammond et al 1996, Rogers 1998, Cromwell et al 2001, Teshima et al 2000. These studies demonstrate that feeding with Roundup Ready® soybeans was substantially equivalent to feeding with traditional soybeans for inducing growth in the animals and the production of milk and fermentation of the cows' rumen.…”
Section: Chemical and Nutritional Equivalencementioning
confidence: 99%
“…Estudos têm também demonstrado claramente que a modificação genética da soja a qual confere tolerância ao herbicida glifosato não afeta a composição nutricional ou o desempenho de animais alimentados com refeições a base de soja, além de não apresentar efeito tóxico (BRAKE; EVENSON, 2004;CROMWELl et al, 2002;JENNINGS et al, 2003). Outros resultados também corroboram a inocuidade de uma variedade de soja nacional GM submetida a ensaios nutricionais com ratos machos durante 14 e 28 dias (CINTRA, 2004;GIORA, 2005).…”
Section: Biossegurança Dos Alimentos Gmunclassified